Plan de negocios para la fabricación y comercialización de bolsos ecológicos hechos con fibra de las hojas de piña para la ciudad de Quito - Palacios Saá, Ursula (2020)
The purpose of this business plan is the production and commercialization of reusable bags based on the pineapple leaf, in the city of Quito. Reusable bags are mainly characterized by not polluting the environment, from their manufacturing process until they are unused and discarded. The reason for the creation Hawaiian bags. Cia. Ltda. Is to offer an alternative to reduce the use of plastic bags that pollute the ecosystem, through an exclusive and quality product made from natural fiber. During the development of the project, various tools were used to determine viability. Analysis of the political, economic, social and technological environment was carried out in order to identify the opportunities and threats that the industry presents and that may be beneficial or a risk for the development of the project. Once the environment was understood, customer research was accomplished to identify acceptance of the product, customer needs and wishes, the target segment, product attributes, price, place, promotion, and the necessary marketing strategies were established. Defined the characteristics of the product, the organizational structure is established along with an operations plan, which is aligned to the needs of the company and customers. Finally, the projected financial model for five years was developed which demonstrates through its results that it is a financially viable project since the financial indicators are positive and the utility is considerably high.